Le concept de « marqueur sub-lexical » : bilan d’un ballon d’essai - Dennis Philps (Anglophonia)
In a 1997 paper, I posited the existence, in the English lexicon, of a word-initial consonant segment which I call a ‘sub-lexical marker’, defined as a submorphemic unit displaying both phonological and notional invariance within the class of words of which it is a formative. Here, I revisit certain aspects of the logic underlying the formulation of this concept (core invariance, variability, embodiment, meaning potential, etc.), and its links, both synchronic and diachronic, with the longer-established concept of ‘phonæstheme’. I go on to show how the discovery of the fundamental role played by analogy in the formation of English ‘sn- words’ led me to reformulate this concept partially, and to reason in terms of subsets. Lastly, I recall the Semiogenetic Theory of the Emergence and Evolution of the Linguistic Sign (STEELS) that evolved from my research into the diachronic dimension of sub-lexical markers.